Charlotte (North Carolina) Spouse Assault Replication Project, 1987-1989 - Hirschel, J. David ([Verlag nicht ermittelbar], 1993)
This study is a replication and extension of an experiment conducted in Minneapolis (MINNEAPOLIS INTERVENTION PROJECT, 1986-1987 [ICPSR 9808]) to test the efficacy of three types of police response to spouse abuse. Three experimental treatments were employed: (1) advising and possibly separating the couple, (2) issuing a citation (an order to appear in court to answer specific charges) to the offender, and (3) arresting the offender. The main focus of the project concerned whether arrest is the most effective law enforcement response for deterring recidivism of spouse abusers. Cases were randomly assigned to one of the three treatments and were followed for at least six months to determine whether recidivism occurred. Measures of recidivism were obtained through official police records and victim interviews. Cases that met the following eligibility guidelines were included in the project: (1) a call involving a misdemeanor offense committed by a male offender aged 18 or over against a female victim aged 18 or over who were spouses, (2) ex-spouses, (3) cohabitants, or (4) ex-cohabitants. Also, both suspect and victim had to be present when officers arrived at the scene. Victims were interviewed twice. The first interview occurred shortly after the "presenting incident," the incident that initiated a call for police assistance. This initial interview focused on episodes of abuse that occurred between the time of the presenting incident and the day of the initial interview. In particular, detailed data were gathered on the nature of physical violence directed against the victim, the history of the victim's marital and cohabitating relationships, the nature of the presenting incident prior to the arrival of the police, the actual actions taken by the police at the scene, post-incident separations and reunions of the victim and the offender, recidivism since the presenting incident, the victim's previous abuse history, alcohol and drug use of both the victim and the offender, and the victim's help-seeking actions. Questions were asked regarding whether the offender had threatened to hurt the victim, actually hurt or tried to hurt the victim, threatened to hurt any member of the family, actually hurt or tried to hurt any member of the family, threatened to damage property, or actually damaged any property. In addition, criminal histories and arrest data for the six-month period subsequent to the presenting incident were collected for offenders. A follow-up interview was conducted approximately six months after the presenting incident and focused primarily on recidivism since the initial interview. Arrest recidivism was defined as any arrest for any subsequent offense by the same offender against the same victim committed within six months of the presenting incident. Victims were asked to estimate how often each type of victimization had occurred and to answer more detailed questions on the first and most recent incidents of victimization.